Biosynthesis and Characterization of an Anticoagulant Chitinase from Fermented Wheat Bran & Shrimp Shells’ Substratum - Meruvu, Haritha; Meruvu, Hari Bhanu Teresa (Trends in Peptide and Protein Sciences, 2019)
Solid state fermentation (SSF) of wheat bran coupled with shrimp shellfish waste Citrobacter freundii str. nov. haritD11 was optimized conventionally (112.43 U/gds) and statistically (124.73 U/gds). Chitinase was purified 4.24-fold with 31% yield and specific activity of 64.87 U/mg protein. The purified chitinase had a specific activity of 64.87 U/mg with optimal activity at pH 9 and temperature 45 ºC. The enzyme was stable at 8.0–9.5 pH range with 90% stability and between 45 °C – 60 °C for 1 hour. The Km value of the Citrobacter freundii haritD11 purified chitinase with swollen chitin (substrate) is 7.53 mg/mL with a Vmax of 2.27 mmol h−1mL−1. The purified chitinase was halotolerant showing maximum activity and stability up to 9% Sodium chloride, it also possessed potential antifungal and anticoagulant activity. This is the first report to date elucidating the production of halotolerant chitinase from wheat bran supplemented with shrimp shellfish waste using Citrobacter freundii haritD11 with notable tolerance to heavy metal ions, its application as an antifungal and anticoagulant agent. HIGHLIGHTS •Optimization of solid-state fermentation of Citrobacter freundii str. nov. haritD11. •The halotolerant chitinase was produced from wheat bran supplemented with shrimp shellfish waste. •The enzyme had notable tolerance to heavy metal ions. •Chitinase was purified 4.24-fold with 31% yield and specific activity of 64.87 U/mg. •The enzyme can be applied as an antifungal and anticoagulant agent.